Faktor-Faktor Yang Mempengaruhi Minat Karir Sebagai Atlet Pada Siswa Tunanetra - Awaludin, Iqbal Indra; Solikah, Nur Luthfiatus; Purnamasari, Ira (JSKK (Jurnal Sains Keolahragaan dan Kesehatan), 2023)
The regeneration of athletes with disabilities is an important point in maintaining sports achievements for people with disabilities, one of which is by depicting the interest of students in special schools to choose careers as athletes. The purpose of this study was to determine the interest of students with visual impairments for a career as athletes. This quantitative descriptive study was conducted using a questionnaire. The researcher assessed blind students (n = 18) who attended in SLBN Citeureup, Cimahi City. The focus of the questionnaire is expressed interest, manifest interest, tested interest, dan inventoried interest. This study shows that blind students are interested in sports (67%) and who want to be an athletes(50%). In general, sports that blind students are interested in are running (33%), swimming (28%), football (22%), while students who did not take part in sports (17%). But all of these students did not take part in special sports training. However 67% of students could show sports techniques and only 56% of students could explain their favorite sport, but 18 students who were interested in running, football and swimming, none of the students took part in matches and had sports achievements. From this study, blind students who enjoy running, football, and swimming do not interested to have a career as an athlete. However, blind students can practice sports belong to what they liked and have an interest in participating in sports activity. Keywords: interest, paralympics, disability, blindness.